Determinants of Masks Purchasing Decisions - Lis Nurkhasanah; Aprih Santoso (Jurnal Studi Manajemen dan Bisnis, 2020)
The purpose of the study was to analyze the effect of product quality, price perception and promotion on purchase decisions. Data collection techniques using questionnaires with a sample of 66 respondents. This study uses multiple regression analysis techniques. The results of this study indicate the quality of the product. perceived price and promotion influence purchase decisions. Product quality variable on purchasing decisions is a significant positive effect. has a standardized estimate (regression weight) of 0.328, (2) the variable price perception on purchasing decisions is a significant positive effect that has a standardized estimate (regression weight) of 0.159, (3) the variable price perception on the purchase decisions is a significant positive effect has a standardized estimate (regression weight) of 0.601.